Hold the fold: how delayed folding aids protein secretion. (31st October 2022) - McCaul, Nicholas; Braakman, Ineke
Abstract : In bacteria, N‐terminal signal peptides mark proteins for transport across the plasma membrane. A recent study by Smets et al (2022) followed the folding of a pair of structural twins to shed light on how evolution has optimised the secretory process. Abstract : A recent study suggests that secreted bacterial proteins may have evolved to fold more slowly than those held in the cytosol.